2018
DOI: 10.1155/2018/6756092
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Extract from Huaier Increases the Expression of Duffy Antigen Receptor for Chemokines and Reduces the Expression of Its Ligands

Abstract: Aims The aim of the present study is to investigate whether the aqueous extract from Huaier, a traditional Chinese medicine (TCM), can affect the expression of Duffy antigen receptor for chemokines (DARC) and its ligands. Moreover, we compare the status of DARC in primary and metastatic breast cancer tissues from the same patient. Methods Immunohistochemistry was used to detect the expression of DARC in primary and metastatic focuses in 30 patients with breast cancer. The effect of Huaier aqueous extract on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previous studies have confirmed that Huaier can play an antitumor role by regulating immune functions, such as increasing the index of immune organs, regulating the number of lymphocytes and regulating the secretion of cytokines. Ying Chen et al [ 28 ] found that Huaier could increase the expression of Duffy antigen receptor for chemokines (DARC) and reduce its ligands, such as CC chemokine ligand 2 (CCL-2), CXC chemokine ligand 8 (CXCL-8, IL-8), matrix metalloproteinase 2 (MMP-2), and CXC chemokine ligand 1 (CXCL-1). DARC plays a negative role in breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that Huaier can play an antitumor role by regulating immune functions, such as increasing the index of immune organs, regulating the number of lymphocytes and regulating the secretion of cytokines. Ying Chen et al [ 28 ] found that Huaier could increase the expression of Duffy antigen receptor for chemokines (DARC) and reduce its ligands, such as CC chemokine ligand 2 (CCL-2), CXC chemokine ligand 8 (CXCL-8, IL-8), matrix metalloproteinase 2 (MMP-2), and CXC chemokine ligand 1 (CXCL-1). DARC plays a negative role in breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…With the finding of role in cancer prevention and treatment, TCM has been one of important alternatives among the new developing anti-tumor drugs possessing low toxicity, side effects, low cost [10]. Huaier extract has been evidenced with anti-tumor effect in numerous in pre-clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many traditional Chinese herbal medicines (TCM) have exerted promising anti-cancer efficacy and applied in clinical settings as complementary anti-tumor agents [10]. Huaier, also known as Trametes robiniophila Murr, has been applied as a TCM for more than 1,600 years.…”
Section: Ivyspringmentioning
confidence: 99%
“…Because the expression of DARC is upregulated but that of its ligand is down-regulated among breast cancer cells in Huaier incubation, Huaier may negatively regulate breast cancer by upregulating DARC ( Figure 2 ). 35
Figure 2 Huaier inhibits cell proliferation and metastasis by upregulating DARC and downregulating its ligands. Huaier suppresses EMT by downregulating twist to inhibit tumor metastasis while the medicine inhibits metastasis by inhibiting c-Myc-Bmi1 signaling pathway.
…”
Section: Breast Cancermentioning
confidence: 99%
“…expression of DARC is upregulated but that of its ligand is down-regulated among breast cancer cells in Huaier incubation, Huaier may negatively regulate breast cancer by upregulating DARC (Figure 2). 35 The mTOR/S6K Signaling Pathway…”
mentioning
confidence: 99%